Testing the content of vitamin A in dietary supplements - Ślifirczyk, Marcin; Jędrzejewska, Barbara; Ślifirczyk, Anna; Denisiuk, Grażyna (Journal of Education, Health and Sport, 2019)
Vitamins in the human body perform regulatory functions, determine the development, health and physical performance of the body. Most of them are not synthesised in the body, therefore they must be supplied with food. They interact with enzymes, which is why they are often called coenzymes or catalysts. Vitamins regulate many life processes. Their deficiency may cause disturbances in metabolic processes and promote the development of various types of diseases.The aim of the work was to analyse the level of vitamin A content available on the Polish pharmaceutical market and dietary supplements.